Perancangan Sistem Electronic Medical Record Rumah Sakit Guna Mempermudah Pengklaiman Terhadap Penjamin Asuransi BPJS - Dede Dwi Aryanto; Besus Maula Sulthon (STMIK Budi Darma, 2023)
Hospitals are Health Facilities or Health Services for the community. In hospitals, medical records are a mandatory and important component that should not be ignored in hospitals. With medical science, law, health technology, and public awareness of their rights, medical record management must change and needs to be done effectively. Moreover, the development of technology and computer devices has become very sophisticated. The aim of the author's research is to make the hospital service process more efficient, including patient satisfaction and speed up the claims process against insurance underwriters, so an adequate and ideal information and communication technology service system is needed, namely an Electronic Medical Record System or medical record application to improve service quality. Apart from that, hospitals must have good medical records to facilitate and speed up the claims process with insurance underwriters. Implementing an electronic medical record system that can help employees no longer record and process medical record data manually. If it runs, there will be changes, namely the faster the process of insurance claims against hospitals and the system which was originally manual will become computerized, thereby speeding up service times at hospitals.